Vibration and Cylinder Chamber Pressure Characteristics of an Air Reciprocating Compressor - Bambang Daryanto Wonoyudo; David A. Siregar (IPTEK Journal of Proceedings Series, 2014)
In the application of a reciprocating compressor failures are often caused by valve malfunction. The failure can be minimized by a proper valve design. This research described an experimental study to investigate characteristics of vibration and cylinder chamber pressure diagrams, as results of open-close valve processes in a single-stage, single-acting air reciprocating compressor. Vibration and pressure were measured at the same crank angle. The modification was materialized by a change in a valve seat profile of a discharge side. The study was conducted for several working loads. Compared to the discharge valve which was (commonly) supplied by the manufacturer, the result showed that a provision of a taper angle on a discharge valve seat would decrease vibration level, made longer discharge opening, and would increase discharge pressure.